The Multifaceted Proprotein Convertases: Their Unique, Redundant, Complementary, and Opposite Functions - Seidah, Nabil G. (American Society for Biochemistry and Molecular Biology, 2013)
The secretory proprotein convertase (PC) family comprises nine members: PC1/3, PC2, furin, PC4, PC5/6, PACE4, PC7, SKI-1/S1P, and PCSK9. The first seven PCs cleave their substrates at single or paired basic residues, and SKI-1/S1P cleaves its substrates at non-basic residues in the Golgi. PCSK9 cleaves itself once, and the secreted inactive protease escorts specific receptors for lysosomal degradation. It regulates the levels of circulating LDL cholesterol and is considered a major therapeutic target in phase III clinical trials. In vivo, PCs exhibit unique and often essential functions during development and/or in adulthood, but certain convertases also exhibit complementary, redundant, or opposite functions.